Efficiency of antiviral treatment in COVID-19 - Negrut, Nicoleta (Exp Ther Med, 2021)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic is responsible for generating a global effort to discover urgent therapeutic solutions to limit the human damage caused by COVID-19. In the period of April to June 2020, 105 patients diagnosed with COVID-19 met the conditions for inclusion in the present study. They were treated with antiviral therapy according to local guidelines: D group (53 cases), treated with darunavir/ritonavir (DRV/r); and K group (52 cases), treated with lopinavir/ritonavir (LPV/r). Patients from the K group required 7.5 days of hospitalization less compared to those from the D group (P<0.001). The blood oxygen saturation values recorded in the groups were statistically different [K group (94.02±3.12%) vs. D group (92.13±4.24%), P=0.010]. The percentage of patients with unsatisfactory clinical evolution were non-significantly higher in the D group compared with the K group [20 (37.74%) vs. 12 (23.08%), P=0.157]. We did not note statistically significant differences between the two groups tracked considering the values for the Brescia-COVID Respiratory Severity Scale (BCRSS) of the patients with unsatisfactory clinical evolution, nor of the chest CT' evolution after 10 days of therapy. We did not register significant adverse effects after antiviral therapy in the two groups. Antiviral therapy with LPV/r had some favorable results compared to DRV/r in patients with COVID-19. Both therapies were well tolerated.